2019
DOI: 10.3390/genes10050392
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Transcriptome Assembly of Protium copal (Burseraceae) and Annotation of Terpene Biosynthetic Genes

Abstract: Plants in the Burseraceae are globally recognized for producing resins and essential oils with medicinal properties and have economic value. In addition, most of the aromatic and non-aromatic components of Burseraceae resins are derived from a variety of terpene and terpenoid chemicals. Although terpene genes have been identified in model plant crops (e.g., Citrus, Arabidopsis), very few genomic resources are available for non-model groups, including the highly diverse Burseraceae family. Here we report the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Instead, it is much more plausible that long distance dispersal into novel habitats and geographic areas was likely the catalyst for initial population isolation followed by lineage 29 divergence. This hypothesis is in line with other studies of diversification of Amazonian taxa, including studies of within species diversification (Damasco et al, 2019;Dexter et al, 2017;Roncal et al, 2015;and discussed in Dick and Pennington, 2019). For instance, a phylogeographic study by Roncal et al (2015) suggested that Astrocaryum sect.…”
Section: Lineage Diversification In Common and Widespread Amazonian T...supporting
confidence: 90%
See 1 more Smart Citation
“…Instead, it is much more plausible that long distance dispersal into novel habitats and geographic areas was likely the catalyst for initial population isolation followed by lineage 29 divergence. This hypothesis is in line with other studies of diversification of Amazonian taxa, including studies of within species diversification (Damasco et al, 2019;Dexter et al, 2017;Roncal et al, 2015;and discussed in Dick and Pennington, 2019). For instance, a phylogeographic study by Roncal et al (2015) suggested that Astrocaryum sect.…”
Section: Lineage Diversification In Common and Widespread Amazonian T...supporting
confidence: 90%
“…Engl. (Damasco et al, 2019) et al, 2014). Detailed methods are provided in the Supplementary Materials.…”
Section: Bait Designmentioning
confidence: 99%
“…In this study, in total, 21 terpenoids were detected ( Table 1 ). Although the genes involved in terpenoid biosynthesis are widely studied in different plants [ 20 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], genes related to the synthesis of terpenoids in sacred lotus have not been studied so far. The precursors of monoterpenes and diterpenes come from the MEP pathway in plastids, while the precursors of sesquiterpenes and triterpenes come from the MVA pathway in the cytoplasm [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clean reads were used to determine alignment counts and to quantify transcript abundance by the RSEM (RNA-seq by Expectation Maximizattion, http://deweylab.github.io/RSEM/) package [37]. The unigene and transcript abundance levels were analyzed by TPM (transcripts per million reads) [38].…”
Section: Differential Transcript Abundance Analysismentioning
confidence: 99%